Genomic technologies to improve variation identification in undiagnosed diseases - Joseph T.C. Shieh (Pediatrics and Neonatology)
Human genome variation has increasingly posed challenges and opportunities for patients, medical providers, and an increasing group of stakeholders including advocacy groups, disadvantaged communities, public health experts, and scientists. Here, advances in genomic sequencing and mapping technologies are discussed with particular attention to the increasing ability to detect personal and population genome variation and the potential for accurate integration of variation into health and disease-related care. Genome mapping, one technique used to create genome map scaffolds, has now been combined with long read sequencing. New technologies have led to improved variation detection, including cryptic structural variation and diverse variants with different degrees of disease association. Combined with advances in automated and medical interpretations, variation detection is increasingly being applied in healthcare. These advances promise to make disease diagnostics more rapid, and potentially more accessible, to those with medical needs. Consequentially, the need for medical genetics and genomics experts is increasing. Here, the opportunities and potential challenges for application of genome-scale variation detection in disease are examined. (<300 words).